The frequency and risk factors of major complications after thermal ablation of liver tumours in 2,084 ablation sessions - Huang, Qiannan; Pang, Mengya; Zeng, Qingjing; He, Xuqi; Zheng, Rongqin; Ge, Mian; Li, Kai (Frontiers in Surgery, 2022)
Background: To assess the frequency of major complications after thermal ablation of liver tumours and to determine risk factors for adverse events. Methods: A retrospective study was conducted between January 2015 and January 2021. A total of 2084 thermal ablation sessions in 1592 patients with primary and metastatic liver tumours were evaluated. The frequency of major complications was evaluated according to the Society of Interventional Radiology Standards, and putative predictors of adverse events were analysed using simple and multivariate logistic regression. Results: Thermal ablation-related mortality was 0.1% (2/2084), with an overall major complication rate of 5.6% (117/2084). The most frequent major complication was symptomatic pleural effusion (2.9%, 60/2084). Multivariate logistic regression analysis revealed that a total maximum diameter of lesions >3 cm, microwave ablation (MWA) and MWA combined with radiofrequency ablation, intrahepatic cholangiocarcinoma and postoperative systemic inflammatory response syndrome were independent prognostic factors for major complications. Conclusions: Thermal ablation of liver tumours is a safe procedure with an acceptable incidence of major complications. The risk factors identified in this study will help to stratify high-risk patients.